Ewolucja poglądów teologicznych na ewolucję - Hałaczek, Bernard (Śląskie Studia Historyczno-Teologiczne, 1998)
The theory of evolution was first introduced in particular circumstances, i.e. when theology was biology-oriented and biology was philosophy-oriented. Leading biologists, especially Ernst Haeckel, regarded it as ultimate confirmation of materialistic monism. Therefore theologiests were strongly opposing it for being an atheistic doctrine. They recognized scriptural description of the creation of Adam as a document of mankind’s origins, supporting at the same time the biological theory of permanence and invariability of species. This led them to erroneus thesis of anthynomy of evolution and creation. Biology – Theology conflict became less serious due to farreaching methodological reflection of these two branches of science on the subject and limits of their cognition. In cours of time biology did not attemt to find full explanation of the origins of all essential human features any more, whilst theology did not try to develop more precise description the „haw” of human origins. Anti-evolutionism in theology was terminated by Humani Generis encyclic by Pius XII in 1950. This encyclic accepts the evolutional interpretation of human origins but it does not accept polygenic one. The Pope justifies the interdiction to propagate polygenism by theological thruth of the original sin which is a hereditory inclination of all people’s (veros homines) to be evil. The are no such concepts as „evil” or „thruth” in natural sciences whereas they are constantly used in theology for description of origins of the First Man. Therefore two separate and quite independent approaches to anthropogenesis can be distinquished: the biological approach and the theological one. Current attitude of Magisterium Ecclesiae towards the theory of evolution was manifested by John Paul’s II message to Pontifical Academy of Science on 28th October 1996. The message makes it quite explicit that „the present state of knowledge enables to recognize the theory of evolution as something more than just only hypothesis”.